Associations Between Life's Essential 8 and Insulin Resistance Among Nondiabetic Adults - Shuo Pang; Yue Wang; Shuaifeng Sun; Shen Wang; Fadong Li; Wenxin Zhao; Xiaofan Wu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Insulin resistance (IR) is closely linked to cardiometabolic diseases. Preventing and improving IR in nondiabetic populations is critically important. We aimed to investigate the relationship between Life's Essential 8 (LE8), the latest tool from the American Heart Association quantifying cardiovascular health, and IR among nondiabetic populations in the United States. Methods and Results This cross‐sectional study used data on 11 246 nondiabetic adults aged ≥20 years from the 2005 to 2018 the National Health and Nutrition Examination Survey. The LE8 score was classified into 2 subscale scores: health factor score and health behavior score. IR was measured by homeostasis model assessment of insulin resistance (HOMA‐IR). Weighted logistic and linear regression models analyzed associations among the LE8 score, health behavior score, health factor score, and IR. Restricted cubic spline models assessed dose–response relationships. Adjusted subgroup analyses and inverse probability of treatment weighting method also evaluated the LE8‐IR relationship. Of the 11 246 participants, 4860 (43.2%) had IR. The mean LE8 score was 70.07 (95% CI, 69.57–70.58). In fully adjusted models, higher LE8 scores were associated with lower IR odds (odds ratio per 10‐unit increase, 0.57 [95% CI, 0.54–0.61]). Nonlinear LE8‐IR dose–response was observed. Similar patterns were seen for health behavior and health factor subscores, with stronger IR correlations for health factors. The inverse LE8‐IR association was significantly more pronounced among White participants and those with higher education, higher income, and without hypertension, cardiovascular disease, or chronic kidney disease. Significant negative LE8‐IR associations persisted after inverse probability of treatment weighting. Conclusions LE8 and subscale scores are negatively associated with IR in a nonlinear relationship. Promoting optimal cardiovascular health adherence may improve IR in nondiabetic populations.